The capacity of Limpopo Provincial Government to implement the provincial growth and development strategy (2004-2014) through strategic planning. - Ravele, Tendani Suzan (My University, 2007)
This study is the first of its kind in the Limpopo Province, consequently, much of its literature focus on Strategic Planning in general. The researcher was motivated to undertake this study due to the manner in which departments were producing Strategic Plans. Different formats were used in departments, Strategic Planning was treated as an add-on activity to personnel, and there is also the lack of alignment and integration between the Strategic Plans and PGDS. The objective of the study is to asses the existing capacity of departments to perform Strategic Planning functions that will inform growth and development in the province; to asses the level of compliance with the Medium Term Strategic Framework; and to recommend strategies to enhance Strategic Planning capacity in departments, thereby ensuring alignment with PGDS. This study, thus examines the capacity of all departments, including the Office of the Premier, to implement the objectives of the PGDS, with specific focus on the Strategic Plans, the type and number of human resources available to perform the duties of Strategic Planning. The researcher follows a qualitative approach. Questionnaires, which comprised both closed and open–ended questions, were e-mailed to 11 provincial department in Limpopo Province and the target respondents were planners, Chief Financial Officers and workstudy officers. Discussions and interviews were conducted with Heads of Departments and Planners, respectively. The results from the SPSS reconciled with the qualitative analysis on open-ended questions show that there is limited planning capacity in the majority of provincial departments in the Limpopo Province. Further research is required with regard to project-specific strategic planning that supports the achievement of the PGDS.
Thesis (M.Dev)--University of Limpopo, 2007.
Keywords: strategic planning; Provincial Growth and Development Strategy; 338.9; Human Development